Impact of genetic deficiencies of P-glycoprotein and breast cancer resistance protein on pharmacokinetics of aripiprazole and dehydroaripiprazole. (October 2014) - Nagasaka, Yasuhisa; Sano, Tomokazu; Oda, Kazuo; Kawamura, Akio; Usui, Takashi
Abstract 1. We investigated how deficiencies in P-glycoprotein (P-gp) and breast cancer resistance protein (BCRP) affect the pharmacokinetics of atypical antipsychotics aripiprazole and its active metabolite (dehydroaripiprazole) using normal Friend leukemia virus strain B (FVB) mice, BCRP knockout (Bcrp[−/−]) mice, and P-gp and BCRP triple knockout (Mdr1a/1b[−/−]Bcrp[−/−]) mice. 2. While plasma concentrations of aripiprazole and dehydroaripiprazole after oral administration were slightly higher in both Bcrp(−/−) and Mdr1a/1b(−/−)/Bcrp(−/−) mice than in normal FVB mice, the difference was not marked. The increase in absolute bioavailability (F) compared with normal mice (approximately 1.3-fold increase) was comparable between Bcrp(−/−) and Mdr1a/1b(−/−)/Bcrp(−/−) mice. This finding suggests that BCRP may be involved in the intestinal absorption of aripiprazole in mice, albeit with minimal contribution to absorption at best. 3. In contrast, the brain-to-plasma concentration ratio (Kp, brain) for aripiprazole and dehydroaripiprazole after oral administration was significantly higher in Mdr1a/1b(−/−)/Bcrp(−/−) mice than in normal mice, whereas Bcrp(−/−) mice exhibited Kp, brain values similar to those in normal mice. In addition, the Kp, brain values in Mdr1a/1b(−/−)/Bcrp(−/−) mice were not drastically different from those previously reported in Mdr1a/1b(−/−) mice, suggesting that brain penetration of aripiprazole and dehydroaripiprazole can be affected by P-gp, but with little synergistic effect of BCRP.